2011
DOI: 10.1017/s0033291711002224
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia, culture and neuropsychology: sensory deficits, language impairments and social functioning in Chinese-speaking schizophrenia patients

Abstract: Our study is the first to investigate an interaction between neuropsychology and language among Mandarin-speaking schizophrenia patients. As predicted, patients were highly impaired in both tone and auditory word processing, with these two measures significantly correlated. Tonally impaired patients showed significantly worse employment-status function than tonally intact patients, suggesting a link between sensory impairment and employment status outcome. While neuropsychological deficits appear similar cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Consistent with other auditory findings, Mandarin-speaking individuals with schizophrenia show notable deficits in the ability both to identify and to discriminate words that are phonemically identical but tonally distinct (for example, ya1 versus ya4). As with deficits in prosodic processing and reading in Western languages, deficits in word discrimination in Mandarin-speaking individuals with schizophrenia markedly correlate both with underlying deficits in tone matching ability and with global measures of psychosocial function such as work status 92 .…”
Section: Behavioural Consequencesmentioning
confidence: 99%
“…Consistent with other auditory findings, Mandarin-speaking individuals with schizophrenia show notable deficits in the ability both to identify and to discriminate words that are phonemically identical but tonally distinct (for example, ya1 versus ya4). As with deficits in prosodic processing and reading in Western languages, deficits in word discrimination in Mandarin-speaking individuals with schizophrenia markedly correlate both with underlying deficits in tone matching ability and with global measures of psychosocial function such as work status 92 .…”
Section: Behavioural Consequencesmentioning
confidence: 99%
“…Neuropsychological evidence showed that prefrontal cortex is closely related to implementation process. Patients with the damage of prefrontal lobe display the decrease of capacity related to judging, organization, planning, decision making, behavioral inhibition and mental damage [29].…”
Section: Functional Changes Of Frontal Lobe In Rat Model Of Schizophrmentioning
confidence: 99%
“…

Cognitive remediation may produce moderate improvements in cognitive function [54]. However, interventions remain difficult to implement, require high levels of patient adherence, and standard approaches have not yet been developed.

Sensory deficits may contribute significantly to social and functional impairments [5557]. Therapies aimed at reversing these deficits, such as music therapy [58] or auditory training [59, 60], may have a significant impact on negative symptoms, depression and social function.
…”
Section: Interventional Proceduresmentioning
confidence: 99%
“…Sensory deficits may contribute significantly to social and functional impairments [5557]. Therapies aimed at reversing these deficits, such as music therapy [58] or auditory training [59, 60], may have a significant impact on negative symptoms, depression and social function.…”
Section: Interventional Proceduresmentioning
confidence: 99%